Language and culture in international legal communication - Kocbek, Alenka (Managing global transitions, 2006)
In the contemporary business world, partners belonging to different nations, and hence different cultures, conduct business operations in either the language of one of the parties involved or in a third, neutral language, serving as lingua franca. Thus, language skills, as an essential component of the communicative competence, imply a certain extent of implicit or explicit translating and interpreting. The functionalist approaches in translation science, and most of all the Skopos theory by J. H. Vermeer, view translation as an intercultural transfer, which inevitably entails taking into account intercultural differences. As intercultural business communication is directly affected by the legal systems of the cultures involved, the communicating parties need to be acquainted with both the source and target legal systems. This is especially the case with English, as the Anglo-American legal system, based essentially on common law, differs substantially from continental law, to which most of the European countries belong. English as the world`s most commonly used lingua franca will have to be adapted to its new function by adopting terms and concepts from other cultures and, within the EU, take into consideration the existing discrepancies between the continental and the Anglo-American legal systems. Inthis paper, cases of non-equivalence regarding legal terms are illustrated with examples from company law. In conclusion, some linguistic and cultural implications of the use of English as lingua franca, as well as their impact on teaching and learning practices are presented.
Keywords: pravosodje; poslovno komuniciranje; pravni jezik; prevajanje; translation; Skopos; angleščina; English